2018
DOI: 10.1007/s13593-018-0508-4
|View full text |Cite
|
Sign up to set email alerts
|

Organic substrate for transplant production in organic nurseries. A review

Abstract: A transplant can be defined as a seedling or sprouted vegetative propagation material grown in a substrate or in the field, for transfer to the final cropping site. Nurseries use a range of growing media in the production of transplants, and the quality of a substrate may be defined in terms of its feasibility for the intended use and also according to the climatic condition of the production site. Peat is the worldwide standard substrate, but because of its origin and the increasing environmental and ecologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 150 publications
(211 reference statements)
5
88
0
5
Order By: Relevance
“…Similarly, the increasing trend of water holding capacity of the substrate with increased organic matter indicates the important property of organic matter in water retention for plant use in favour of biosolids application. In line with this study, Pascual et al (2018) reported that easily available water in a substrate should range from 20 to 30%. These results were found to be with the ideal water holding capacity of 40-65% that corresponds with water retention of 25-30% (Abad et al, 2001).…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, the increasing trend of water holding capacity of the substrate with increased organic matter indicates the important property of organic matter in water retention for plant use in favour of biosolids application. In line with this study, Pascual et al (2018) reported that easily available water in a substrate should range from 20 to 30%. These results were found to be with the ideal water holding capacity of 40-65% that corresponds with water retention of 25-30% (Abad et al, 2001).…”
Section: Discussionsupporting
confidence: 82%
“…Cocopeat is widely used as a component of nursery substrates (Salvador et al, 2005) because of its relatively high waterholding capacity and good cation exchange capacity. Perlite has very low bulk density and high porosity to supply aeration (Bunt, 1988;Pascual et al, 2018). A mixture of these two compositions is commonly used in soilless culture.…”
Section: Resultsmentioning
confidence: 99%
“…Biostimulants such as Radifarm ® may help tomato roots develop during plantlet growth, especially when growing conditions at this stage are not optimal for young plants (Parađiković, Vinković, Teklić, Guberac, & Milaković, ; Table a). By definition, a transplant is a seedling or sprouted vegetative propagation material grown in a substrate or in a field which is supposed to be transferred to the final cropping site (Pascual et al., ). After this process, the transplants enter a very sensitive growth period—they have to adapt to new environmental conditions, which may slow down their growth and development.…”
Section: Biostimulant Effects On Edible Horticultural Speciesmentioning
confidence: 99%
“…Nowadays, horticultural production has to cope with the increasing challenges of meeting high productivity with global demands for environment‐friendly crop management practices. In organic agriculture, the use of chemical fertilizers and pesticides is limited (Pascual et al., ), so there is a need for different plant amendments suitable for such production. In the face of degraded agricultural areas and uncertainties related to the changing climate, biostimulants use can be an interesting option.…”
Section: Introduction To the Biostimulants Application In Plant Produmentioning
confidence: 99%